2016
DOI: 10.1039/c6cc03578g
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a [Dy(OH2)8]3+ cation: magneto-optical and theoretical studies of a caged, emissive SMM

Abstract: The first supramolecular cage formed by three benzo-15-crown-5 macrocycles encapsulating a [Dy(OH2)8](3+) guest cation is reported, with the Dy(iii) centre exhibiting local pseudo square antiprismatic D4d symmetry. The anisotropy barrier extracted from ac susceptibility studies, emission spectroscopy and ab initio calculations reveals that the second excited state Kramers doublet plays a key role in the magnetization dynamics due to the Ising character and near coparallel nature of the ground and first excited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…The energy gaps between highest and lowest Stark components of 4 F 9/2 level determined as the difference between A 1 * and A 1 and B 1 * and B 1 transitions are equal to 84±12 and 96±16 cm −1 , respectively. These values are coherent with the previously reported data [5c,f] . It could be observed that the energy gaps to bridge the first excited Kramers doublets of the 6 H 15/2 state to the ground doublet were U A =84±9 and U B =70±10 cm −1 .…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…The energy gaps between highest and lowest Stark components of 4 F 9/2 level determined as the difference between A 1 * and A 1 and B 1 * and B 1 transitions are equal to 84±12 and 96±16 cm −1 , respectively. These values are coherent with the previously reported data [5c,f] . It could be observed that the energy gaps to bridge the first excited Kramers doublets of the 6 H 15/2 state to the ground doublet were U A =84±9 and U B =70±10 cm −1 .…”
Section: Figuresupporting
confidence: 93%
“…The emission decay curves measured in the solid state at 77 K to determine the 4 F 9/2 → 6 H 13/2 lifetime (Figures S11–S13, Supporting Information) gave typical values for dysprosium‐based complexes values of 0.112±0.002, 0.167±0.005 and 0.160±0.001 ms, respectively for 1 , 2 and 3 [5c,f] …”
Section: Figurementioning
confidence: 99%
“…This confirms that the main source of relaxation is clearly an Orbach process (red dashed line, Figure 5b). This constitutes a rare example of a luminescent SIM without an underestimation of ∆ obtained by magnetism as frequently observed in luminescent SIMs [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 57%
“…In this line of scope, luminescent SIMs are particularly appropriate for these investigations since the photo-luminescence measurements permit determining spectroscopically the Stark sub-level structure of the lanthanides ions and comparing it with the magnetic data. However, examples of such magneto-optical correlations are rather scarce [7][8][9][10][11][12][13][14][15][16][17][18] in comparison with the large number of reported lanthanides-based SIMs. This fact is often due to the weak or completely quenched emission in these complexes.…”
Section: Structurementioning
confidence: 99%
“…We have been interested for long in such correlation between magnetism and luminescence, and it has been exemplified several times within the past ten years. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, lanthanide single ion anisotropies are strong enough to permit the observation of a SMM behaviour even for mononuclear complexes, provided naturally that quantum tunnelling of magnetisation (QTM) is not too effective. 23 These mononuclear SMM are very interesting from a fundamental point of view.…”
Section: S1 Introductionmentioning
confidence: 99%